INCORPORATION OF UNCERTAINTY IN TECHNICAL AND ECONOMIC ANALYSIS OF A FELLER-BUNCHER - Simões, Danilo; Miyajima, Ricardo Hideaki; Tonin, Rodrigo Petrongari; Fenner, Paulo Torres; Batistela, Gislaine Cristina (Floresta, 2018)
The constant technical and economic analysis of timber harvesting operations is essential and determining, due to the monetary magnitude. Traditionally, these analyses are conducted deterministically, which does not allow obtaining values with probabilities of occurrence. Considering this issue, stochastic models were built in order to analyze the behavior of probabilistic production cost in felling operations with feller-buncher, through the Monte Carlo method. The study was conducted in the Central-West region of the state of São Paulo in a forest of Eucalyptus sp., with six years of age, planted in 3 x 2 m spacing. Technical analysis was based on the study of time and movements, which determined the effective productivity and economy in the hourly operating cost of the feller-buncher and in the production costs of the operation. Due to uncertainties, probability distributions were assigned to these results, which identified the most relevant variables and quantified the probabilities of the production cost. The results demonstrated that the fuel cost had a statistically significant strong positive correlation coefficient ( = 0.91) (p-value < 0.01). The hourly cost, consequently, was directly proportional to the production cost of the operation. The production cost of the operation in flat relief was 18% lower than the production cost of the operation in undulating relief.